Maternal wellbeing: a concept analysis - Bahuguna, Ekta; Pugazhendi, Sanchita; Juyal, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Pregnancy and childbirth cause many physiological, psychological and social changes thus it is considered as critical period in every woman’s life. Wellbeing during perinatal period is influenced by many factors as it is a unique and complex process. Therefore, importance of conceptualizing concept of maternal wellbeing has recently gained attention. Objective of study is to provide more precise definition of concept maternal wellbeing. Walker and Avant method of concept analysis, was adapted to facilitate concept analysis on maternal wellbeing. Electronic bibliographic database was searched to identify the published paper related to the maternal wellbeing; which includes: (Google scholar, PubMed, Taylor and Francis, Ovid) and websites (WHO, Maternal and child health bureau (MCHB), NHM). By undertaking a detailed literature review attributes, antecedents, consequences and empirical referents of maternal wellbeing were identified. The attributes of maternal wellbeing during perinatal period includes: cognitive/affective self-evaluation of life, and multidimensional elements (physical, social, psychological, economical. This concept analysis will provide new insight into maternal wellbeing concept used for midwives and nurses in their practice. Also, findings can help expand or develop theories and models for improving maternal wellbeing during perinatal period.